Compositions Study and Analyzing the Performances of Lakorn Nok (Royal’s Style) from the Story of Mahabharata Episode Cursing Arjun - Sekthanachotchinda, Grittaychin (Journal of Fine and Applied Arts Khon Kaen University, 2024)
The study of composition and analyzing the performances and drama role story of Mahabharata episode cursed Arjun. The objectives of the study were 1) to study the elements and analyze the performance of a non-royal drama and 2) to analyze the elements of a non-royal drama. For this study, the researcher used a qualitative research by using documentary research by document analysis Creative research. The results of the study found that; 1. Compostion of the Royal theatrical performances has existed since the Rattanakosin period enhanced from the Noh Rachatree drama, popular drama and using pure male, compostion has costumes, bands, venues, and outside plays are for fun and entertainment. Fast-paced and funny, used words in the play are villagers words. 2. Drama role story of Mahabharata episode cursed Arjun was found that it was a drama outside the royal style. It is a drama that has been improved from the original foreign drama that has existed since the Ayutthaya period. The characteristic of foreign dramas is that the story moves quickly. But there is a descriptive process. Example, admiring characters, admiring nature or places. The bathing ceremony is according to the style of the drama and has funny lines without obscenity. The elements of the Mahabharata drama, the episode Cursing Arjuna, have the characteristics of such non-royal dramas. Expresses the idea that gambling is something that causes loss of everything and makes life miserable. Like Arjuna who had to be cursed by the angel Uravasi to become a hermaphrodite